2012
DOI: 10.1039/c2cc32595k
|View full text |Cite
|
Sign up to set email alerts
|

A homochiral metal–organic framework membrane for enantioselective separation

Abstract: For the first time, a homochiral metal-organic framework membrane was prepared for the enantioselective separation of important chiral compounds, especially chiral drug intermediates, which will allow for the potential development of a new, sustainable and highly efficient chiral separation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(90 citation statements)
references
References 28 publications
1
89
0
Order By: Relevance
“…Because of a stronger binding energy, (R)-enantiomer is more predominantly adsorbed than (S)-enantiomer, which is consistent with experiment. Our previous simulation studies 52,53 also revealed that the interaction between enantiomer and chiral adsorbent is crucial in enantioselective adsorption. Furthermore, Supplementary Fig.…”
Section: Synthesis and Characterization Of The Mofsmentioning
confidence: 99%
“…Because of a stronger binding energy, (R)-enantiomer is more predominantly adsorbed than (S)-enantiomer, which is consistent with experiment. Our previous simulation studies 52,53 also revealed that the interaction between enantiomer and chiral adsorbent is crucial in enantioselective adsorption. Furthermore, Supplementary Fig.…”
Section: Synthesis and Characterization Of The Mofsmentioning
confidence: 99%
“…The approach appears to be better suited to metal organic framework (MOF) films and membranes made by stepwise deposition of reactants, liquid phase epitaxy and other layer-by-layer assembly approaches. [51][52][53][54][55][56][57][58] 2.2.3. Varying temperature hot dip coating.…”
Section: Tsapatsismentioning
confidence: 99%
“…However, polymer membranes usually bear a trade-off between selectivity and permeability [15]. Due to the good affinity of their structures with polymer chains, MOF particles are considered as good fillers for the fabrication of mixed matrix membranes (MMMs) toward gas separation [10]. Although the related investigation on polymer/MOF composite membranes is still in an early stage, some computational studies have shown that such types of MMMs can exhibit great superiority over the corresponding pure polymeric membranes [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs), as a novel class of crystal nanoporous materials, have attracted tremendous interest in the membrane-based gas separation and purification during the past decade [7][8][9][10]. Considering the large number of existing materials, it would be very time consuming to experimentally examine the separation properties of new MOF-based membranes.…”
Section: Introductionmentioning
confidence: 99%